Probiotics in the 21st century - Malm, Anna; Łoś, Renata; Jach, Monika; Szymańska, Jolanta; Gziut, Nina (Polish Journal of Public Health, 2010)
An adequate style of life, including the proper diet determining composition of natural microflora of host organism, mainly intestinal microflora, has fundamental significance for health of both individuals and a population. Probiosis, i.e. “improvement” of intestinal microflora composition, associated with an increase of probiotics – the friendly bacteria possessing the favourable interactions with a host organism, appears to be not only an alternative method against the pathogenic microorganisms but also as a manner for “health and long life” in 21th century. “Probioticotherapy” may include an use of exogenous probiotics, prebiotics stimulating growth of endogenous probiotics, or synbiotics, i.e. exogenous probiotics together with the appropriate prebiotics. In this article an review of actual knowledge concerning probiotics and their impact on human health is presented.